A Missense Mutation in the MYBPH Gene Is Associated With Abdominal Fat Traits in Meat-Type Chickens - Trevisoli, Priscila Anchieta; Moreira, Gabriel Costa Monteiro; Boschiero, Clarissa; Cesar, Aline Silva Mello; Petrini, Juliana; Margarido, Gabriel Rodrigues Alves; Ledur, Mônica Corrêa; Mourão, Gerson Barreto; Garrick, Dorian; Coutinho, Luiz Lehmann (Frontiers in Genetics, 2021)
Chicken is an important source of protein for human nutrition and a model system for growth and developmental biology. Although the genetic architecture of quantitative traits in meat-type chickens has been the subject of ongoing investigation, the identification of mutations associated with carcass traits of economic interest remains challenging. We performed a genome-wide association analysis (GWAS) for breast, thigt and drumstick traits in meat-type chickens and detected 19 unique QTL. We then used: 1) the identified windows; 2) QTL for abdominal fat detected in a previous study with the same population and 3) previously obtained whole genome sequence data, to identify 18 predicted deleterious SNPs in those QTL for further association with breast, tight, drumstick and abdominal fat traits. Using the additive model, a predicted deleterious SNP c.482C>T (SIFT score of 0.4) was associated (p-value <0.05) with abdominal fat weight and percentage. This SNP is in the second exon of the MYBPH gene, and its allele frequency deviates from Hardy–Weinberg equilibrium. This gene was previously associated with intramuscular fat deposition in cattle and with muscle development in chickens. In conclusion, our study provides evidences that the c.482C>T SNP in the MYBPH gene is a putative causal mutation for fat deposition in meat-type chickens.